SECURE VERTEX-EDGE DOMINATION IN HYPERCUBE AND GRID GRAPHS: APPLICATIONS OF CYBERSECURITY IN BANKING FOR SECURE TRANSACTIONS - C. Ruby Sharmila; S. Meenakshi (Journal of Mechanics of Continua and Mathematical Sciences, 2025)
In the banking sector, safeguarding sensitive financial transactions is critical to maintaining customer trust and regulatory compliance. Cybersecurity threats, ranging from data breaches to unauthorized access, necessitate robust protective measures. However, the majority of research places a strong emphasis on vertex dominance in security networks while ignoring the importance of edge defense for overall security, also hypercube and grid structures are not considered. Furthermore, conventional studies have ignored the potential of hypercube and grid graph structures in enhancing security measures. Hence this research proposed a secure vertex-edge domination (SVED) in hypercube and grid graphs, exploring their applications in optimizing cybersecurity measures for secure transaction monitoring. Moreover, develop a Hidden Markov Model (HMM) framework to enhance the detection of anomalous activities within these graph structures. This algorithm efficiently computes the minimum number of security agents required to monitor transaction flows, thus reducing vulnerabilities. This research not only fills a critical gap in existing network security methodologies but also proposes a novel framework for protecting complex networks from evolving cyber threats, thereby advancing the frontier of cybersecurity and mathematical graph theory.